1990
DOI: 10.1177/001698629003400305
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Social Status of Gifted Students by Their Age Peers

Abstract: This study investigated the social status of gifted children enrolled in an educational pull-out program with same-aged peers not identified as gifted. Both groups completed a sociometric nomination instrument in which they rated classmates. Results were analyzed in terms of the percentage of students assigned to popular, rejected, or neglected categories by peers. A 2 (gifted) x 2 (gender) analysis was used. Gifted boys were most popular while gifted girls were least popular. Boys and girls not identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 13 publications
0
28
0
3
Order By: Relevance
“…O fato de os resultados mostrarem que alunos com D&T não diferem significativamente dos pares sem D&T no que se refere à quantidade de amigos que possuem, bem como ao envolvimento com bullying, pode ser considerado um indicador de que esses estudantes possuem um nível de habilidades socioemocionais pelo menos equivalente ao dos alunos não identificados com D&T. Isso tem sido demonstrado na literatura sobre ajustamento socioemocional desses indivíduos (Lehman & Erdwins, 2004;Luftig & Nichols, 1990). Porém essas inferências devem ser alvo de estudos adicionais, já que não foram contempladas outras dimensões do desenvolvimento socioemocional (personalidade, habilidades sociais, etc.)…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O fato de os resultados mostrarem que alunos com D&T não diferem significativamente dos pares sem D&T no que se refere à quantidade de amigos que possuem, bem como ao envolvimento com bullying, pode ser considerado um indicador de que esses estudantes possuem um nível de habilidades socioemocionais pelo menos equivalente ao dos alunos não identificados com D&T. Isso tem sido demonstrado na literatura sobre ajustamento socioemocional desses indivíduos (Lehman & Erdwins, 2004;Luftig & Nichols, 1990). Porém essas inferências devem ser alvo de estudos adicionais, já que não foram contempladas outras dimensões do desenvolvimento socioemocional (personalidade, habilidades sociais, etc.)…”
Section: Discussionunclassified
“…Já os alunos com D&T eram percebidos como menos propensos a estarem envolvidos com o fenômeno. Esses resultados parecem ser coerentes com outras pesquisas que afirmam que estudantes com D&T tendem a apresentar maiores estratégias de enfrentamentos e resolução de problemas sociais (Preuss & Dubow, 2004), maiores níveis de empatia e de raciocí-nios pró-sociais (Hay, 2008) e altos níveis de aceitação dos colegas (Luftig & Nichols, 1990), se comparados aos pares sem características de D&T.…”
unclassified
“…While our qualitative inquiry revealed that Playful Booth data are likely to reflect actual social groupings, our quantitative analysis suggested that data derived from Playful Booth and ones derived from self-reports, such as the Peer Nomination Inventory [9] may reflect different facets of social participation in school communities. Our future work will focus on a more elaborate analysis on the quantitative data that was beyond the scope of the current paper.…”
Section: Discussionmentioning
confidence: 78%
“…Social participation was measured using Luftig's and Nichols' Peer Nomination Inventory (PNI) [9]. PNI consists of six questions in which students nominate classmates "with whom they wish to interact in a variety of social situations or which they like 'best' and like 'least' in the class" [9].…”
Section: Field Deployment Of Playful Boothmentioning
confidence: 99%
See 1 more Smart Citation